Radiological maps in beach sands along some coastal regions of Turkey. Issue 1 (15th November 2016) - Kucukomeroglu, B.; Karadeniz, A.; Damla, N.; Yesilkanat, C.M.; Cevik, U.
Abstract: In the present research, the gamma-emitting radionuclides in beach sands along the coastal regions of the Ordu, Giresun and Trabzon provinces, Turkey have been determined. The natural and anthropogenic radionuclide concentrations of the samples have been measured employing a germanium (HPGe) detector with high resolution and purity. The activity for 238 U, 232 Th, 40 K and 137 Cs of the samples were found to vary in the range from below detection limit (BDL) to 65 Bq·kg − 1, from BDL to 28 Bq·kg − 1, from 9 to 1936 Bq·kg − 1 and from BDL to 22 Bq·kg − 1, respectively. The activity concentrations were compared with those in the literature. The associated radiological hazard indices were estimated, and were compared to the internationally recommended values. The radiological map of beach sand in the surveyed area was imaged. The data presented in the study are crucial since they constitute a baseline for the radiological mapping of the region in the future. Highlights: The natural and anthropogenic radionuclide concentrations in beach sands were analyzed. The associated radiological hazard indices were estimated. The results were evaluated to check the compatibility of national and international values. The radiological maps of beach sand were produced. The findings demonstrate that the obtained values were less than the internationally accepted recommended limits.